Flow Cytometry Analysis of Free Intracellular NAD+ Using a Targeted Biosensor. Issue 1 (17th December 2018) - Eller, Jared M.; Stewart, Melissa L.; Slepian, Alexandria J.; Markwardt, Sheila; Wiedrick, Jack; Cohen, Michael S.; Goodman, Richard H.; Cambronne, Xiaolu A.
Abstract: Flow cytometry approaches combined with a genetically encoded targeted fluorescent biosensor are used to determine the subcellular compartmental availability of the oxidized form of nicotinamide adenine dinucleotide (NAD + ). The availability of free NAD + can affect the activities of NAD + ‐consuming enzymes such as sirtuin, PARP/ARTD, and cyclic ADPR‐hydrolase family members. Many methods for measuring the NAD + available to these enzymes are limited because they cannot determine free NAD + as it exists in various subcellular compartments distinctly from bound NAD + or NADH. Here, an approach to express the sensor in mammalian cells, monitor NAD + ‐dependent fluorescence intensity changes using flow cytometry approaches, and analyze data obtained is described. The benefit of flow cytometry approaches with the NAD + sensor is the ability to monitor compartmentalized free NAD + fluctuations simultaneously within many cells, which greatly facilitates analyses and calibration. © 2018 by John Wiley & Sons, Inc.